Two women in the Klondike - Hitchcock, Mary E., author; University of Alaska Press, publisher (Colorado State University. Libraries, 2005)
Two Women in the Klondike created a sensation when it was first published in 1899. The idea that two well-bred socialites could survive the dangers of the north thrilled nineteenth-century readers from San Francisco to New York.
Ho for the land of gold! -- With malice towards none -- Land in sight! -- St. Michaels -- A trial of patience -- We meet old friends -- Transferred at last -- We hear the signal -- Up the Yukon -- Discomfort of barge life -- Nearing our destination -- The promised land -- We become squatters -- The "sick boy" -- Our first dinner in Dawson -- We become "free miners" -- Visiting mines with a Klondike king -- Our man Friday -- Isaacs, the irrepressible -- Our helpful neighbours -- A new scheme -- The rideout at last -- Trials of building -- Business propositions -- A new experience -- In the new home at last -- A series of disappointments -- Adieu to Dawson -- The race with the Domville -- The first portage -- The Skaguay Pass -- A day in Sitka -- Killisnoo -- Farewell to Alaska.
This volume is an abridgement of the original 1899 edition.
Keywords: Hitchcock, Mary E. (Mary Evelyn), 1849-1920; Castelmenardo, Edith Van Buren, contessa, -1914; Women pioneers -- Yukon -- Klondike River Valley -- Biography; Women pioneers -- Alaska -- Biography; Frontier and pioneer life -- Yukon -- Klondike River Valley; Frontier and pioneer life -- Alaska; Klondike River Valley (Yukon) -- Gold discoveries; Alaska -- Gold discoveries; Klondike River Valley (Yukon) -- Biography; Alaska -- Biography